Role of Institutions and Organizations for the Sustainable Management of Forest and Pasture as Common Property Resources in Nepal: An Overview of the Indigenous and Traditional Practices - Uprety, Laya Prasad (Dhaulagiri Journal of Sociology and Anthropology, 2008)
This is an overview paper based on the contemporary literature available in the regime of forest and pasture as common property resources. The analysis has underscored the role of local institutions and organizations for the sustainable management of forest and pasture as common property resources. The paper concludes that farmers of Nepal have developed and used the organizational and institutional mechanisms for the sustained management of these resources by ensuring social equity. Understanding the ingredients of indigenous resource management systems can have a bearing on developing appropriate national policies aiming at ensuring the sustainability of the future programs of Nepal. Key Words: Institution, organization, indigenous, traditional, common property, sustainable, social equity, participation, etc. DOI = 10.3126/dsaj.v2i0.1357 Dhaulagiri Journal of Sociology and Anthropology Vol.2 pp.31-64